Islamic Education in Indonesia and Malaysia: Shaping Minds, Saving Souls by Azmil Tayeb - Hew Wai Weng (Kajian Malaysia, 2019)
There are many historical studies on Muslim connections in Southeast Asia that examine Muslim societies in the region including of both present-day Malaysia and Indonesia. Yet, many contemporary studies on Muslim societies in this region focus on a single country. Azmil Tayeb’s book Islamic Education in Indonesia and Malaysia: Shaping Minds, Saving Souls stands out as one of the recent comparative scholarly works that bring these two neighbouring countries together. The book is theoretically engaged, empirically rich and analytically persuasive, examining the nexus of state-society relations in managing religious education. Thus, it not only benefits researchers in the studies of Muslim societies and political Islam, but also those interested in comparative politics, state-society relations and religious education.